How to be Norwegian in talk? Polish-Norwegian interethnic conversation analysis - Horbowicz, Paulina (Novus Press, 2010)
The present contribution deals with the topic of cultural preconditions of talk and can therefore be placed within the broad field of CA. The data material collected for the study consists of dyadic conversations between native and Polish (hence non-native) speakers of Norwegian. This setting allows the author to compare the language use of both interlocutors and to draw conclusions as to what can be identified as speaking practices typical for Norwegian discourse. Against the background of existing sociological and anthropological research, the study describes the Norwegian ethnic communication pattern and analyses the consequences of its existence for speakers of Norwegian as a second language.
It is a ph.d.-dissertation, defended at Adam Mickiewicz University in 2009, and published in Norway in 2010.
Keywords: conversation analysis; Norwegian conversation; non-native conversation; ethnic communication pattern; Norwegian as a second language; speaking practices